The dynamic treatment of SARS-CoV-2 disease. Issue 4 (1st October 2020) - Sandkovsky, Uriel; Colley, Peter; Sam, Teena; Modrykamien, Ariel M.; Berhe, Mezgebe
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or novel coronavirus disease 2019 (COVID-19) emerged from China in December 2019 and progressed to become a global pandemic. Our understanding of its pathophysiology and potential management was initially extrapolated from previous epidemics of coronaviruses like SARS and MERS. SARS-CoV-2 is asymptomatic or minimally symptomatic in more than 80% of patients and requires no additional management; however, the remaining patients progress to pneumonia and hypoxemia with ranging severity, including a smaller group that requires intensive care unit admission. To date, there are no approved treatments for SARS-CoV-2, and current management is focused on supplemental oxygen and supportive care. The antiviral medication remdesivir recently received emergency use authorization by the US Food and Drug Administration for patients with severe disease. Multiple clinical trials evaluating different treatment modalities such as antivirals, immunomodulators, convalescent plasma, and monoclonal antibodies, among others, are still ongoing. We believe that patients present with clinical phenotypes that correlate with the spectrum of disease. Each phenotype may benefit from one or multiple interventions. We discuss treatments under evaluation in clinical trials and their potential application based on clinical phenotype presentation.